2015
DOI: 10.18520/cs/v109/i12/2299-2302
|View full text |Cite
|
Sign up to set email alerts
|

Flower Sex Expression in Cucurbit Crops of Kerala: Implications for Pollination and Fruitset

Abstract: Cucurbits are monoecious in general; the female flowers occur lower than the male flowers in fields. Often farmers are not aware of this type of sex expression, and are concerned about the low fruit set despite 'profuse' flowering and abundant pollinators in the crop fields. We assessed flower sex expression during the peak (female) flowering and fruiting period in three widely grown cucurbit crops, Cucurbita maxima, Benincasa hispida and Momordica charantia in a village ecosystem of northern Kerala. Sex expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…We found that ants occupied more than 75% of the owers during the early hours of anthesis in different elds. The ratio of staminate owers to pistillate owers counted in our study agrees that the number of staminate owers is mostly higher in a eld 25,33,34 . As the nectar amount varies between the staminate and pistillate owers, this might be a major determinant of ant infestation of owers.…”
Section: Discussionsupporting
confidence: 89%
“…We found that ants occupied more than 75% of the owers during the early hours of anthesis in different elds. The ratio of staminate owers to pistillate owers counted in our study agrees that the number of staminate owers is mostly higher in a eld 25,33,34 . As the nectar amount varies between the staminate and pistillate owers, this might be a major determinant of ant infestation of owers.…”
Section: Discussionsupporting
confidence: 89%
“…Greenhouse cultivation has the advantage of crop production during temperate winters when Gac is otherwise dormant [7]. Hand pollination can also be required when the pollen resource is limited, which can be a problem for cucurbit crops when pollinators are not present to transport pollen or when sex-expression is variable and biases the production of male or female flowers [12]. In one example, in several expansive plots within a Cucurbita maxima crop, only female flowers were observed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hand pollination can also be required when the pollen resource is limited, which can be a problem for cucurbit crops when pollinators are not present to transport pollen or when sex-expression is variable and biases the production of male or female flowers [12]. In one example, in several expansive plots within a Cucurbita maxima crop, only female flowers were observed [12]. Gac crops are not excluded from variable sex expression, having been observed with male flowers appearing first [7] or female flowers appearing first in the season [13].…”
Section: Introductionmentioning
confidence: 99%